Critical approach of the use of economic models in precautionary risk management - Gonçalves, V. (2013)
In this article a synthesis of formal models for the economic interpretation of the precautionary principle is presented, with their virtualities, limitations and measures to overcome them. The concept of precaution has great relevance in environmental regulation in the European Union. On the one hand, and despite the somewhat vague nature of legislation, the interpretation of the precautionary principle has seen recent progress with the development of some economic models and their application. There is, however, a need for a regulatory framework for the implementation of this principle in environmental decision-making, i.e., to clarify concepts and management procedures that are appropriate to the nature of environmental risks. It is therefore important to know the most relevant economic approaches and models with the aim of identifying their contribution to the debate on precaution in the context of environmental risk management and discuss their practical relevance in public decision-making.